Sequence‐based identification, genotyping and EUCAST antifungal susceptibilities of Trichosporon clinical isolates from Greece. (22nd January 2014) - Arabatzis, M.; Abel, P.; Kanellopoulou, M.; Adamou, D.; Alexandrou‐Athanasoulis, H.; Stathi, A.; Platsouka, E.; Milioni, A.; Pangalis, A.; Velegraki, A.; Lass‐Florl, C.
Abstract Trichosporon yeasts constitute emerging pathogens, implicated in organ‐specific and systemic infections. In this first, comprehensive study of Trichosporon clinical isolates in Greece, 42 isolates were identified by sequencing the hypervariable D1/D2 domain of the Large Subunit (LSU) rDNA gene, while Trichosporon asahii were genotyped by sequencing the Intergenic Spacer 1 region, and antifungal susceptibilities were determined by the EDef 7.2 (EUCAST) method, in parallel with the CLSI standard. Trichosporon asahii was the primary species (37 isolates) followed by Trichosporon coremiiforme, Trichosporon dermatis, Trichosporon loubieri and Trichosporon mycotoxinivorans. One strain remained unidentified. Seven T. asahii genotypes were recorded. The major genotypes were: genotypes 4 (29%) and 3 (26%) followed by 1, 5 and 7 (9.5% each). Two novel genotypes were identified designated as 10 and 11. EUCAST MIC ≥2 mg/L was recorded in 58% of the isolates (amphotericin B), 41% (itraconazole), 41% (posaconazole) and 38% (voriconazole). Fluconazole MICs of ≥32 mg/L were recorded in 23.8% of the isolates. Analysis of variance performed on absolute values showed that the amphotericin B, itraconazole, posaconazole and voriconazole MICs of T. asahii were equivalent. Typically higher MIC values were displayed by fluconazole. Antifungal susceptibilities of the seven different genotypes were homogeneous. Agreements between EUCAST and CLSI ranged from 88.1 to 97.62%. Overall, the high MICs recorded among the Trichosporon isolates for all tested drugs justify routine susceptibility testing of clinical isolates.